From the Polish Minister of Environment - Nowicki, Maciej (Problemy Ekorozwoju, 2009)
We are supporting and taking an interest in the initiative to bring the State Environmental Council within the team editing and publishing Problemy Ekorozwoju – Problems of Sustainable Development, a journal that has clearly now taken its rightful place in the international hierarchy of such works. It is thanks to this publication that the world has a better and fuller presentation of environmental thinking in Poland, via both scientific papers and the informing of public opinion on State Environmental Council activity within the European Environment and Sustainable Development Advisory Councils (EEAC) framework. It just remains for me to wish the editorial team fulfilled expectations as regards the new-formula publication, and all readers success for 2009, in “friendly” social and natural surroundings.